2013
DOI: 10.1093/eurjhf/hft018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNAs serve as biomarkers of therapeutic efficacy and disease progression in hypertension‐induced heart failure

Abstract: AimsRecent studies have shown that microRNAs (miRNAs), besides being potent regulators of gene expression, can additionally serve as circulating biomarkers of disease. The aim of this study is to determine if plasma miRNAs can be used as indicators of disease progression or therapeutic efficacy in hypertension-induced heart disease. Methods and resultsIn order to define circulating miRNAs that change during hypertension-induced heart failure and that respond to therapeutic treatment, we performed miRNA arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
3
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 28 publications
10
105
3
2
Order By: Relevance
“…Increases in circulating miRNAs upon cell damage have been detected by RT-PCR-based approaches for liver, brain, and skeletal muscle (5), as well as heart (19,46 instances miRNAs even performed better than established protein biomarkers (5). Our analysis indicated that heart-specific myomirs performed similar to the highly sensitive cTnI assay, but we were unable to verify the utility of any recently proposed miRNA biomarker for HF (18,(20)(21)(22). Considering that sRNAseq experiments capture a wide spectrum of miRNAs as well as fragments of other classes of RNAs, and can be performed with low ng quantities of total RNA recoverable from 250 μL plasma or serum, this approach holds great potential for future RNA biomarker discovery.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Increases in circulating miRNAs upon cell damage have been detected by RT-PCR-based approaches for liver, brain, and skeletal muscle (5), as well as heart (19,46 instances miRNAs even performed better than established protein biomarkers (5). Our analysis indicated that heart-specific myomirs performed similar to the highly sensitive cTnI assay, but we were unable to verify the utility of any recently proposed miRNA biomarker for HF (18,(20)(21)(22). Considering that sRNAseq experiments capture a wide spectrum of miRNAs as well as fragments of other classes of RNAs, and can be performed with low ng quantities of total RNA recoverable from 250 μL plasma or serum, this approach holds great potential for future RNA biomarker discovery.…”
Section: Discussionmentioning
confidence: 85%
“…S1) were shown to contribute to muscle or myocardial function (8, 9). miRNAs and other classes of RNA have been profiled in failing human myocardium (10)(11)(12)(13)(14)(15)(16)(17), and a selected subset was also investigated as circulating biomarkers in HF (18)(19)(20)(21)(22)(23)(24). However, in these studies heart tissue and circulating miRNA abundance changes were not acquired simultaneously to correlate changes in tissue versus circulating miRNA composition.…”
mentioning
confidence: 99%
“…[24] Interestingly, it was also noted that these microRNAs increased during disease progression and were reduced in response to treatment with ACE inhibitor. [24] Whilst the limitations of an animal model must be accepted, this work highlights great potential for microRNAs to not only act as biomarkers of target-organ damage, but also of disease progression and response to treatment.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
“…[24] Interestingly, it was also noted that these microRNAs increased during disease progression and were reduced in response to treatment with ACE inhibitor. [24] Whilst the limitations of an animal model must be accepted, this work highlights great potential for microRNAs to not only act as biomarkers of target-organ damage, but also of disease progression and response to treatment. More recently, Sanchez-de-la-Torre et al screened 84 'cardiovascular' microRNAs to identify a panel of three plasma microRNAs whose pre-treatment levels could accurately predict blood pressure lowering response to continuous positive airway pressure (CPAP) in patients with resistant hypertension and obstructive sleep apnoea.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
“…In recent years, numerous studies have addressed the association between dysregulated miRNAs and LV hypertrophy in the context of HF in animals and humans. In a study carried out on a hypertension-induced HF mouse model using polymerase chain reaction analysis for a selected panel of miRNAs it was demonstrated that circulating levels of miR-16, miR-20b, miR-93, miR-106b, miR-223, and miR-423-5p were significantly increased in response to hypertension-induced HF, while this effect was blunted in response to treatment with antimiR-208a as well as an angiotensin-converting enzyme inhibitor [11]. Endo et al [1] demonstrated through miRNA array analysis that miRNA-15a and b, miR-20a, miR-103, miR-130a and b, miR-195, miR-210, miR-301b, miR-451, and miR-494 were dysregulated in rats with HF.…”
Section: Resultsmentioning
confidence: 99%